The Role of the Palm Oil Industry in Malaysia's Socioeconomic Development: Challenges and Educational Implications - Shehu, Sani (Universitas Pendidikan Ganesha, 2024)
The oil palm tree originates from West Africa and was introduced to Malaysia in the early 1870s by a British individual. In 1917, a Frenchman named Henry Fouconnier became the first to plant oil palm commercially in Tennamaram, Selangor. The production of palm oil has since become a cornerstone of Malaysia's socioeconomic development. It serves as one of the nation’s primary income sources, driving economic growth, generating revenue, and alleviating poverty. This paper explores the pivotal role of the palm oil industry in Malaysia’s socioeconomic landscape, despite challenges such as limited land for expansion. The study employs a qualitative approach, utilizing document analysis and semi-structured interviews for data collection. Inductive thematic analysis was conducted using Atlas.ti to analyze the data. The findings highlight the significant contributions of the palm oil industry, including providing food for human consumption, creating employment opportunities, generating income for farmers, supplying raw materials for industries, alleviating poverty, enhancing living standards, supporting renewable energy sectors, and contributing to economic growth. In conclusion, the palm oil industry plays a vital role in Malaysia's socioeconomic development. These findings underscore the importance of incorporating such industrial contributions into educational curricula to foster a comprehensive understanding of sustainable economic practices.